Fenomenología : Steven Holl = Fenomenology : Steven Holl.
Tres museos realizados por el estudio de Steven Holl: Nelson-Atkins Museum of Art, Kansas City (Missouri), Nanjing Museum of Art & Architecture (Nanjing, China), Herning Center of the Arts (Herning, Denmark)